2020
DOI: 10.1536/ihj.19-489
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-Modified Albumin Is Associated with Arterial Stiffness in Hemodialysis Patients

Abstract: Increased arterial stiffness is strongly associated with cardiovascular morbidity and mortality in dialysis patients. Ischemia-modified albumin (IMA) is a useful biomarker of cardiac ischemia. This study was aimed to explore the association between IMA and arterial stiffness in hemodialysis patients. An observational study was conducted with 120 hemodialysis patients. Clinical data and laboratory characteristics were collected. Arterial stiffness was evaluated by brachial-ankle pulse wave velocity (baPWV). Hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In ESRD patients, Sharma et al found that high IMA levels were correlated with a significantly larger left ventricular size, decreased left ventricular systolic function, and increased mortality [ 18 , 19 , 20 ]. Recently, it has been shown that high IMA is associated with vascular oxidative stress and inflammation [ 38 , 39 ], and some novel data pointed out that IMA is a good predictive marker of arterial stiffness in hemodialysis patients [ 40 ]. Increased arterial stiffness is a frequent finding in hemodialysis patients and is involved in high CV morbidity [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In ESRD patients, Sharma et al found that high IMA levels were correlated with a significantly larger left ventricular size, decreased left ventricular systolic function, and increased mortality [ 18 , 19 , 20 ]. Recently, it has been shown that high IMA is associated with vascular oxidative stress and inflammation [ 38 , 39 ], and some novel data pointed out that IMA is a good predictive marker of arterial stiffness in hemodialysis patients [ 40 ]. Increased arterial stiffness is a frequent finding in hemodialysis patients and is involved in high CV morbidity [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specific posttranslational modifications of proteins in human studies and potentially as a diagnostic method are technically evolving [149]. In the case of oxidation, a few clinically relevant oxidized proteins are known: One important protein in which redox modification has been associated with poor prognosis in several diseases is albumin [150,151]. When ROS increases in the circulation, redox changes in the metal and fatty acid-binding sites of albumin decrease, increasing the oxidative potential of these free molecules.…”
Section: Oxidation Productsmentioning
confidence: 99%
“…Of note, continuous ventilation led to lower levels of IMA 24 h after CBP suggesting that lung ventilation during the operation could reduce ischemia and lung damage reducing the drop of blood flow (Ozgunay et al, 2019). In a recent paper, IMA has been described, in hemodialysis patients as a good predictor of arterial stiffness, which is strongly associated with cardiovascular risk in this type of patients (Jiao et al, 2020).…”
Section: Albumin Oxidative Modifications and Cvd: The Contribution Of Msmentioning
confidence: 99%